Rotting plants protect grain - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Rotting plants give off carbon dioxide (CO2) which can help to control pests of stored grain. Putting decomposing vegetable matter with stored grain provides a cheap pest control system. Maintaining high concentrations of CO2 in grain stores is a...